AKAR KULTURAL DALAM PUISI KARYA PEREMPUAN PENYAIR BERETNIS MADURA: KAJIAN ANTROPOLOGI SASTRA - Anwar, M Shoim (ATAVISME, 2022)
Madura has a distinct subculture in Indonesian culture. Poetry by female Madurese poets can also represent this distinctive anthropological cultural aspect. From the perspective of literary anthropology, with a qualitative approach, the aims of this reasearch are to interpret, analyze, and find things related to anthropological cultural roots in poetry by women of Madurese ethnic poets. The result of this research is that the poetry of Madurese ethnic women poets is influenced by the anthropological cultural journey based on Madura, both when the poets live on the island of Madura and when they are in other places. The anthropological cultural aspect that appears is the existence of various events in the past which are used as sources of ideas for creation, especially when they were children.  The dominant cultural types in poetry  by women of Madurese ethnicity are those to art, livelihood or economy, relationships in social organization  or familial relationships, and religion as cultural shield.